2007
DOI: 10.1590/s0103-50532007000800012
|View full text |Cite
|
Sign up to set email alerts
|

LaFe xMn yMo zO 3 catalysts for the oxidation of volatile aromatic organic contaminants

Abstract: Novas perovskitas mistas LaFe x Mn y Mo z O 3 foram preparadas, caracterizadas e investigadas como catalisadores para a oxidação total de tolueno, usado como composto orgânico aromático volátil (COV aromático) modelo. As perovskitas foram caracterizadas por DRX (Difratometria de Raios X), RTP (Redução a Temperatura Programada), determinação de área superficial BET e espectroscopia Mössbauer. Os dados obtidos indicaram a formação da fase perovskita e a incorporação de todos os metais na estrutura. As reações ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…62,63 Magnetite showed a high activity for the oxidation of carbon monoxide at lower temperatures, being related to the presence of surface Fe 2+ species capable of activating gas phase O 2 to form more reactive species. 64,65 Magnetite doped with Mn or Co, Fe 3-x M x O 4 (M = Mn, Co; x = 0-0.75) was also used as catalyst to high selective oxidation of β-pinene, a renewable monoterpene, under solvent free conditions.…”
Section: Catalytic Applications Of Iron Based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…62,63 Magnetite showed a high activity for the oxidation of carbon monoxide at lower temperatures, being related to the presence of surface Fe 2+ species capable of activating gas phase O 2 to form more reactive species. 64,65 Magnetite doped with Mn or Co, Fe 3-x M x O 4 (M = Mn, Co; x = 0-0.75) was also used as catalyst to high selective oxidation of β-pinene, a renewable monoterpene, under solvent free conditions.…”
Section: Catalytic Applications Of Iron Based Materialsmentioning
confidence: 99%
“…The improvement of the catalytic activity was discussed in terms of the effect of Fe on the creation of surface and structural defects which can increase the perovskite reactivity towards oxygen. 63,65 Iron was also used as catalyst associated with materials such as clays. The pillared clay montmorillonite containing highly dispersed iron oxide showed very good activity and stability for the oxidation of toluene.…”
Section: Catalytic Applications Of Iron Based Materialsmentioning
confidence: 99%
“…In this work, Co oxide was used as the coupling species with cerium or lanthanum in Co-Ce or Co-La mixed oxides. Cerium oxide is often used for VOC oxidation, either as a support or mixed with other metal oxides [4,16,[42][43][44][45][46][47][48][49][50][51][52][53]; however not many studies are found in literature for lanthanum oxides [54][55][56][57][58]. The obtained catalysts were tested in the oxidation of toluene (C 7 H 8 ), which has a vapour pressure of 2.734 kPa at 20°C [59].…”
Section: Introductionmentioning
confidence: 99%